Pediatric intestinal obstruction: analysis of etiologies and factors influencing short-term outcomes in Rwanda - Jennifer Rickard; Edmond Ntaganda; Isaie Twahirwa; Cyriaque Ndayiragije; Martin Nyundo (BMJ Publishing Group, 2022)
Background Intestinal obstruction is a common presentation in pediatric surgical emergencies and presents with different etiologies depending on country or region. Its morbidity and mortality are high in low-income and middle-income countries, with variable influencing factors. The aims of this study were to determine the etiologies, morbidity and mortality of pediatric intestinal obstruction and to assess the factors associated with the outcomes of these conditions in Rwanda.Methods This was a cross-sectional study conducted on pediatric patients with intestinal obstruction in two Rwandan university teaching hospitals. The patients were followed from admission until discharge, and we documented their basic characteristics, diagnosis, operative details and postoperative outcomes. Data were collected using data collection form and were electronically captured and analysed using SPSS software.Results A total of 65 patients were enrolled in this study. They were predominantly male (n=49, 75.4%), and the majority of patients (86.2%) were below age 6 years. Intussusception was the most common etiology (n=22, 33.8%). Other common etiologies were Hirschsprung's disease (n=13, 20%), incarcerated inguinal and umbilical hernias (n=6, 9.2%), intestinal worms' impaction (n=5, 7.7%) and adhesions (n=5, 7.7%). Mortality and morbidity were 9.2% and 39.7%, respectively. The most common complications were surgical site infection (n=6, 9.5%) and sepsis (n=6, 9.5%). Preoperative anemia (p=0.001), finding of gangrenous bowels (p=0.003) and bowel resection at the time of laparotomy (p=0.039) were factors associated with postoperative complications.Conclusions The etiologies of intestinal obstruction are variable and common in children below 6 years in Rwanda. The associated morbidly is high and is influenced by the preoperative anemia, finding of gangrenous bowels and bowel resection.